Crack growth direction effects on corrosion-fatigue behaviour of offshore wind turbine steel weldments. (January 2021) - Jacob, Anais; Mehmanparast, Ali
Abstract: In this study corrosion-fatigue tests have been conducted on fracture mechanics specimens extracted from an S355 G10+M structural steel welded plate. The tests have been performed on compact tension specimens with the crack tip located in the heat affected zone. The corrosion-fatigue test results from this study have been compared with the data available on the base metal as well as air tests on the same material. Moreover, the obtained results have been compared with the corrosion-fatigue data available in the literature on a wide range of steels and also the fatigue trends for welded joints in free-corrosion condition recommended in the BS7910 Standard. The effect of the specimen orientation, with respect to the weld region, is also examined in this study and it has been found that higher corrosion-fatigue crack growth rates are generally observed in the tests with 0° orientation. The results have also shown that the corrosive environment has significant effects on the fatigue crack growth acceleration at the beginning of the tests; however, as the crack propagates, the environmental damage effect on crack growth behaviour becomes less pronounced. The results presented in this study are discussed in terms of improvement in the structural integrity assessment of offshore wind turbine monopiles. Highlights: Corrosion-fatigue tests have been performed on C(T) HAZ specimens extracted from an S355 G10+M welded plate. The experimental results have shown that the FCG rates in seawater are sensitive to the specimen orientation. Conservative analysis of the remaining life in OWT monopiles can be conducted using the Paris-law constants obtained from 0° orientation samples. The obtained results show that the corrosive environment accelerates the FCG behaviour, particularly at lower ΔK values. Corrosion effects have been found to diminish as the crack propagates and the ΔK value subsequently increases.